Therapeutic drug monitoring of lacosamide among children: is it helpful? - Kohn, Elkana; Lezinger, Mirit; Daniel, Sharon; Masarwi, Majdi; Brandriss, Nurit; Bar-Chaim, Adina; Berkovitch, Matitiahu; Heyman, Eli; Komargodski, Rinat (Frontiers in Pharmacology, 2023)
Objective: This study aimed to investigate the efficacy and tolerability of Lacosamide (LCM) in a pediatric population with epilepsy using LCM serum concentration and its correlation to the age of the participants and the dosage of the drug. Methods: Demographic and clinical data were collected from the medical records of children with epilepsy treated with LCM at Shamir Medical Center between February 2019 to September 2021, in whom medication blood levels were measured. Trough serum LCM concentration was measured in the biochemical laboratory using High-Performance Liquid Chromatography (HPLC) and correlated with the administered weight-based medication dosing and clinical report. Results: Forty-two children aged 10.43 ± 5.13 years (range: 1–18) were included in the study. The average daily dose of LCM was 306.62 ± 133.20 mg (range: 100–600). The average number of seizures per day was 3.53 ± 7.25 compared to 0.87 ± 1.40 before and after LCM treatment, respectively. The mean LCM serum concentration was 6.74 ± 3.27 mg/L. No statistically significant association was found between LCM serum levels and the clinical response (p = 0.58), as well as the correlation between LCM dosage and the change in seizure rate (p = 0.30). Our study did not find a correlation between LCM serum concentration and LCM dosage and the gender of the participants: males (n = 17) females (n = 23) (p = 0.31 and p = 0.94, respectively). A positive trend was found between age and LCM serum concentrations (r = 0.26, p = 0.09). Conclusion: Based on the data that has been obtained from our study, it appears that therapeutic drug monitoring for LCM may not be necessary. Nonetheless, further research in this area is needed in the light of the relatively small sample size of the study.